Social Competence and Language Skills in Mandarin–English Bilingual Preschoolers: The Moderation Effect of Emotion Regulation. Issue 3 (2nd April 2016) - Ren, Yonggang; Wyver, Shirley; Xu Rattanasone, Nan; Demuth, Katherine
Abstract: Research Findings : The main aim of this study was to examine whether language skills and emotion regulation are associated with social competence and whether the relationship between English skills and social competence is moderated by emotion regulation in Mandarin–English bilingual preschoolers. The language skills of 96 children ages 36–69 months from Australian child care centers were assessed using standardized English and Mandarin tests. Social competence was assessed using teacher reports on the Behavior Assessment System for Children–2 (BASC-2) with 4 composite scales: Externalizing, Internalizing, Behavioral Symptoms, and Adaptive Skills. Positive emotion regulation and emotion dysregulation were assessed using the disappointing gift task and teacher report on the Emotion Regulation Checklist. The results show that positive emotion regulation, emotion dysregulation, English skills, and Mandarin skills were associated with different composites of the BASC-2; the relationships between English skills and Behavioral Symptoms were moderated by positive emotion regulation; and English skills and Adaptive Skills were moderated by emotion dysregulation. Practice or Policy : Discussion of the results includes new considerations for a focus on emotion regulation as well as language to promote social competence in bilingual children.